Tinjauan Literatur: Analisis Sintesis dan Efektivitas Senyawa Kalkon serta Turunannya sebagai Agen Antibakteri - Damara , Dandy Satria; Akifah , Muthia Nur; Putri , Indah Syah; Utami , Marsah Rahmawati (Journal of Pharmaceutical and Sciences, 2025)
Chalcones are flavonoid compounds that have attracted attention in the development of antibacterial agents. This literature review aims to examine the synthesis and effectiveness of chalcone compounds and their derivatives as antibacterials. Through descriptive analysis, chalcone synthesis was carried out using several methods, one of which was the condensation between benzaldehyde and acetophenone, followed by structural modification to produce various chalcone derivatives. The antibacterial activity of chalcone compounds and their derivatives was tested against bacteria such as S. aureus, E. coli, B. substillis, and other types of bacteria. The results of the review of several literatures obtained online through Google, Google Scholar, and Publish or Perish were carried out using the keywords "Synthesis", "Chalcone", and "Antibacterial" with publications from the last 10 years (2014-2024) with a total of 8 references used. The study showed that changes in the structure of chalcones, such as the addition of hydroxyl and methoxy groups, can affect antibacterial activity. Some chalcone derivatives also showed promising antibacterial activity, although their effectiveness varied depending on the type of bacteria tested.